Genetic characterization of Koraput sheep of Odisha - sanjeev singh; KN Raja; Indrajit Ganguly; Reena Arora; Sanat Mishra (Journal of Livestock Biodiversity, 2025)
A survey was conducted in the native breeding tract of the Koraput sheep in Odisha for the phenotypic characterization of this lesser known sheep population. Information on body biometry of 127 adult animals was collected from 21 sheep farmers. Comparison of body biometry measures of Koraput sheep with Ganja msheep found in the same area revealed that Koraput sheep has lower average measures for body weight, body length, height at wither, chest girth, ear length and horn length.Moreover, the phenotypic appearance (notched ears, small body size and variations in coat colour) of this sheep population is also distinct from the Ganjam breed. Koraput sheep therefore has the potential to be recognised and registered as a distinct breed.